Don't Let the Memories Fly Away (3): Hilmi Çelik That I Used to Know... - Ahmet Karataş (Türk Kütüphaneciliği)
In the article penned due to the passing of Hilmi Çelik, the doyen colleague of ours, he is commemorated through his humanitarian, professional and literary sides.